Character strengthening through the development of a P5 RA module based on local wisdom in Bojonegoro traditional cuisine - Sa’diyah, Zumrotus; Fithriyah, Dewi Niswatul (Mitra PGMI: Jurnal Kependidikan MI, 2025)
This character development can be carried out through the Project for Strengthening the Pancasila Student Profile and the Rahmatan Lil Alamin (P5 RA) which is based on local regional wisdom. Bojonegoro is an area rich in local wisdom such as batik and typical food. However, the majority of students have low knowledge and skills in understanding local wisdom. So, there is a need for a P5 RA module based on local wisdom. The aim of this research is to develop a phase B P5 RA module based on local wisdom. This module will highlight material about Bojonegoro Traditional Cuisine. This research uses the ADDIE method with detailed stages of analysis, design, development, implementation and evaluation. The research results showed that the module developed had high validity in terms of content, language and visual design, and received positive responses from teachers and students. The implementation of the module succeeded in increasing students' understanding of Pancasila values ​​and the local culture of Bojonegoro. This research recommends the use of similar modules as part of contextual learning in the Merdeka Curriculum.